High Anal Canal Pressure and Rectal Washouts Contribute to the Decrease of Anal Basal Pressure After Botulinum Toxin Injections in Paediatric Patients With Chronic Constipation - Sun, Ge; Trzpis, Monika; Broens, Paul M. A. (Frontiers in Pediatrics, 2022)
Abstract Introduction: Chronic constipation can be treated by injecting botulinum toxin into the anal sphincter to decrease anal basal pressure. To assess the effect of botulinum toxin, we investigated the factors that contribute to changes in anal basal pressure after injection. Methods: This was a retrospective study conducted in a tertiary hospital in the Netherlands. We included children with chronic constipation treated with botulinum toxin injections and measured anal basal pressure before and after each injection. Multivariable linear regression analyses were used. Results: We investigated 30 cases with idiopathic constipation. Their median age was 20.5 (7.75-53.25) months. Anal basal pressure decreased after injection in 20 cases. The mean decrease of anal basal pressure after injection was 18.17 + 35.22 mmHg. The anal basal pressure change was linearly correlated with preinjection pressure (R2 = 0.593, P < 0.001). A significant decrease of pressure was observed in patients with preinjection pressure > 70 mmHg. Preinjection anal basal pressure (β = -0.913, P < 0.001) and rectal washouts (β = -21.015, P = 0.007) contributed significantly to pressure changes. Changes in anal basal pressure were also significantly associated with patients’ weights (β = 0.512, 95% CI, 0.011 - 1.013) and sex (β = 22.971, 95% CI, 9.205 - 36.736). Conclusions: Botulinum toxin significantly decreases anal basal pressure when preinjection pressure is higher than 70 mmHg. In patients with severely elevated anal basal pressure, we recommend rectal washouts to promote the decrease of anal basal pressure.